EFFECT OF PREDICT, OBSERVE, AND EXPLAIN (POE) LEARNING MODEL ON STUDENT’S LEARNING ACTIVITIES AND MASTERING OF FOOD DIGESTION SYSTEM CONCEPTS - Adhitian Adhitian; Arwin Achmad; Tri Jalmo (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
The results of interviews with teachers in high school biology class XI Swadhipa Natar, it is known that subjects, especially biology subject matter Digestive System Food is delivered by using the method of discussion. Though this material has special characteristics that examine the mechanisms of complex processes that are difficult to understand, and involve organs that correspond to the structure and function of complex. The purpose of this study is to determine effect of Predict, Observe, Explain And (POE)  learning model  on student’s  learning activities  and mastering  of  Food Digestion System  concepts  of  Swadhipa  high school students. This  a quasi-experimental  strudy  used pretest-posttest  with non-equivalent dsigned. The  sample   were  students of  class   XI IPA2 as the experimental group and class XI IPA1 as a control  which was  selected from the population at random cluster sampling. Data was collected   as  in  percentage form.   The students’ actvities observed consists of five (5)  abilities of predicting, observing, describing, working together, and making conclusion. The study resulted that POE learning model  could enhanced the students’  predicting  ability  up to 20%,  observing ability up to 19%, describing ability up to 24%,  abity to work together up to 22,8%, and  ability of making onferences up to 16%